Aratati ca numarul : a=(√3 +√5) · (3 - √15) + (1 - √3)² + 4√3 este natural
Răspunsuri la întrebare
Răspuns de
9
a=(√3 +√5) · (3 - √15) + (1 - √3)² + 4√3 =
=3√3 +3√5 - √45 - √75 + 1 - 2√3+3 + 4√3 =
=3√3 +3√5 - 3√5 - 5√3 + 1 - 2√3+3 + 4√3 =
=1
=3√3 +3√5 - √45 - √75 + 1 - 2√3+3 + 4√3 =
=3√3 +3√5 - 3√5 - 5√3 + 1 - 2√3+3 + 4√3 =
=1
Alte întrebări interesante
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă